A journey towards a safe harbour: The rhetorical process of the International Integrated Reporting Council. Issue 2 (March 2020) - La Torre, Matteo; Dumay, John; Rea, Michele Antonio; Abhayawansa, Subhash
Abstract: This paper investigates the rhetoric deployed by the International Integrated Reporting Council (IIRC) to legitimise itself and Integrated Reporting () and establish its ideology. We draw on Aristotle's rhetorical appeals – ethos, logos, and pathos – and the rhetorical theory of diffusion to conduct a rhetorical analysis of the IIRC's initial documents. Our findings demonstrate how the IIRC's rhetorical strategies serve to: authorise and moralise the IIRC's actions through ethos and pathos ; contrast certain social interests and privilege a capitalist ideology through logos ; and establish and maintain the IIRC's authority in a way that reflects the interests of the financial community and investors, again, through ethos . We demonstrate how the IIRC has strategically used rhetoric to gain support and develop its authority by contrasting and resisting competing ideological pressures. We also show how a capitalist ideology emerged from this struggle as the shaping force behind at the cost of marginalising wider social interests. Examining the IIRC's rhetorical process contributes to understanding the ideological struggle surrounding and enriches our empirical understanding of the ideological turn of rhetorical strategies. Our study contributes to theory and practice by advancing knowledge on the rhetorical strategies that shape and establish dominant ideologies in accounting practice.